Scenes from Old Russian History in Book Illustration of the 1750s-Early 1830s: On the Specifics of Subjects - Skvortcova, Ekaterina A. (Actual Problems of Theory and History of Art, 2024)
Whereas the theme of Old Russian history in academic painting and sculpture of the 2nd half of the 18th ‒ 1st third of the 19th century has justly attracted considerable scholarly attention, the prints and, specifically, book illustrations dealing with the same subject have remained largely ignored. The paper presents the results of the research which revealed 37 editions dating from the 1750s to the 1830s and illustrated with scenes from Old Russian history. Only a minority of works in question pertain to history (7).  They are of interest primarily from the point of view of visual studies, as illustrations had a much wider scope than painting or sculpture and consequently played a significant role in the development of national identity. The gradual formation of national-state narrative resulted in greater attention to state-forming events (in this respect the themes of illustration are similar to those addressed in academic programs) and the pre-Slavic past on the territory of future Russia. Some subjects are evocative of the 18th-century tradition of interpreting history as a collection of didactic events. The illustrations to fiction (30 editions) are of interest also from the point of view of art history as they foreshadow trends which later, from the mid-19th century, would become typical for painting: the interpretation of large-scale historical events projected to the fate of particular characters, eventless history genre dealing with manners and customs of the past, interest to negative characters and dramas around them. The accompanying fiction on the Old Russian theme with a series of three to four illustrations presenting scenes which became conventional at the turn of the 1820 and the 1830s influenced the practice of illustrating works on history and culminated in the grandiose edition of “Painted Karamzin” (1836‒1844).The research was financed by the grant of the Russian Scienсe Foundation, № 24-28-00856, https://rscf.ru/project/24-28-00856/
Keywords: Old Russia; history; Russian literature; Russian art; printed editions; illustrations; engraving